TINDAKAN YURIDIS PEMERINTAH DAERAH DALAM PENERTIBAN PEKERJA ANAK JALANAN BERDASARKAN PERATURAN DAERAH NOMOR 16 TAHUN 2002 DI KOTA SAMARINDA - Andi Septian Noor (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACT Research on street children dilaksanankan on the field and in the municipal police in the city of Samarinda LPA ( child protection agency ) , and NGO Insan Insan Borneo . The purpose of this research is to know about the condition , the problems facing street children and the constraints that dihadapu by Samarinda City Government to implement the Local Regulation . 16 Year 2002 on Street Children , especially to meet the kesejahteraanya as a child . The research method that I use is normative juridical method which is a form of research that basically took the sources of collecting data and studying the books in the library that there kaitanya the researchers, and research Juridical Empires is a form of research on suaru basically take the sources through field research with government agencies related to child Countermeasures terlantur . Data collection techniques using primary data collection and secondary data . And the results of a survey conducted on the streets to meet the child who addressed the rights and obligations of data about 188 children were scouted from the NGO that the top of the Regional Regulation 16 of 2002 affect the provisions of partially defined peace and public order .